PENGAWASAN OJK ATAS DATA PRIBADI KONSUMEN PADA PERUSAHAAN PEER TO PEER LENDING - Nursantih, Nadia; Ratnawati, Elfrida (UNES Law Review, 2023)
Peer to peer lending providers require consumer personal data to conduct funding, this is very important to pay attention to the protection of personal data, because in the use of personal data due to the possibility of misuse of user personal data. The government issued a new policy due to problems and issues over the misuse of personal data by issuing and passing Law Number 27 of 2022 concerning the protection of personal data. The formulation of the problem discussed, how is the Legal Protection of Consumers Regarding the Misuse of Personal Data in Peer to peer lending Transactions and the Financial Services Authority Supervision of Peer to peer lending Business Activities related to Consumer Protection of Personal data. Normative writing method, with, descriptive nature of writing, type of data using secondary data, qualitative data analysis. And conclusion making is done with deductive logic. Based on the results of the study, Legal Protection of Consumers regarding Misuse of Personal Data in Peer to peer lending transactions, regulated by Law Number 27 of 2022 and also regulated in POJK 10/2022, the two regulations regulate the prohibitions and obligations of Peer to peer organizers in terms of protection in personal data management and regulate the sanctions obtained in the event of misuse of personal data and POJK No.6/POJK.07/2022 is a form of OJK's efforts in organizing integrated supervision of Peer to peer lending companies.